EUPHEMISM PRACTICE BY CRAIG FERGUSON FOR JOKING FASHIONED UTTERANCES IN THE LATE SHOW - CLAUDIA SARI, RENNY (LANGUAGE HORIZON, 2019)
Abstract Euphemism Practice by Craig Ferguson for Joking Fashioned utterances in the Late Show Name : Renny Claudia Sari Registration Number : 15020154070 Study Program : S-1 Department : English Literature Faculty : Languages and Arts University : State University of Surabaya Advisor : Lina Purwaning Hartanti, S.Pd., M.EIL. Keywords: euphemism, joke, Late Show Language is simple way to communicate with someone else to deliver something not only orally but also written. . On the other hand, language also can be used to make known how your personality is, so that is why every person needs to choose which words that are match for speaking with. In this case, researcher takes euphemism as the theory and explains more about the types of euphemism, the meaning relation of euphemistic and the function of euphemism. It can be seen from the tittle of the research namely, Euphemism Practice by Craig Ferguson for Joking Fashioned in the Late Show. This research uses qualitative approach to answer the research questions. Qualitative approach is chosen as the methodology to analyze the data findings because it is the most suitable method to answer the research questions of the study. This research uses euphemism to analyze the video uttered by Craig Ferguson in the Late Show. This research showed four types of euphemism out of five. It can maintain good relationship between Craig Ferguson and his guests while in the Late Show. In this case, the researcher also did not find all types of euphemism but she only some. Abstrak Praktik Eufemisme oleh Craig Ferguson sebagai ucapan gaya bercanda di Late Show Name : Renny Claudia Sari Nomer Resigstrasi : 15020154070 Program Belajar : S-1 Prodi : Sastra Inggris Fakultas : Bahasa dan Seni Universitas : Universitas Negeri Surabaya Pembimbing : Lina Purwaning Hartanti, S.Pd., M.EIL. Bahasa adalah cara sederhana untuk berkomunikasi dengan orang lain dan menyampaikannya tidak hanya secara lisan tetapi juga tulisan. Di sisi lain, bahasa juga dapat digunakan untuk mengungkap kepribadian seseorang, sehingga setiap orang perlu memilih kata yang cocok dalam berbicara. Dalam hal ini, peneliti mengambil eufemisme sebagai teori dan menjelaskan lebih banyak tentang jenis eufemisme, makna hubungan eufemik dan fungsi eufemisme. Hal ini dapat dilihat dari judul penelitian yaitu, Praktik Eufemisme oleh Craig Ferguson untuk ucapan gaya bercanda di Late Show Penelitian ini menggunakan pendekatan kualitatif untuk menjawab pertanyaan penelitian. Pendekatan kualitatif dipilih sebagai metodologi untuk menganalisis temuan data karena merupakan metode yang paling cocok untuk menjawab pertanyaan penelitian. Penelitian ini menggunakan eufemisme untuk menganalisis video yang diucapkan oleh Craig Ferguson di acara Late Show. Penelitian ini menghasilkan empat tipe dari lima tipe yang menghasilkan kata-kata eufemisme yang diucapkan oleh Craig Ferguson di Late Show. Hal tersebut, membuat hubungan antara Craig Ferguson dan tamunya berjalan dengan baik. Dalam hal ini, peneliti juga tidak menemukan semua jenis eufemisme tetapi ia hanya menemukan beberapa jenisnya saja.